Computer-Generated Speaker Charisma and Its Effects on Human Actions in a Car-Navigation System Experiment - or How Steve Jobs’ Tone of Voice Can Take You Anywhere - Niebuhr, Oliver; Michalsky, Jan (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2019)
A particularly persuasive (charismatic) tone of voice has a far reaching influence on people’s opinions and actions. However, does this also apply if the charismatic tone of voice is produced by a computer, and if this computer asks people to act against better knowledge? Addressing these questions, an experiment was set up in which 30 locals of Sonderborg/DK were asked to conduct a test drive with a car from the marina to the university campus of the city. The test drive was conducted on the pretext of assessing a newly developed retrofit car navigation system that provides voice instructions only. The locals did not know that the system was only a remote-controlled mock-up that, moreover, started giving its driver wrong instructions after about half of the trip. The instructions got successively falser, until the only option to get to the university campus was to make a complete U-turn. We measured the point at which the drivers aborted the test drive in two conditions. In the first one, the system spoke with the more charismatic tone of voice of Steve Jobs. In the second one, it spoke with the less charismatic tone of voice of Mark Zuckerberg. Results show that drivers followed the navigation system’s increasingly worsening instructions significantly longer in the Steve Jobs condition, and that the system received higher quality, trustworthiness, and purchase ratings if it spoke with Steve Jobs’ tone of voice. Results are discussed in terms of persuasive technology and implications for charisma/leadership analyses and training.
CRIS-Team Scopus Importer:2019-07-26
Keywords: Mark zuckerberg; Navigation system; Prosody; Speaker charisma; Steve jobs; Text-to-speech-synthesis; Tone of voice

Pascal and DPA: A pilot study on using prosodic competence scores to predict communicative skills for team working and public speaking - Niebuhr, Oliver; Michalsky, Jan (Proceedings of the Annual Conference of the International Speech Communication Association, INTERSPEECH, 2019)
Strong communication skills in public-speaking and team-working exercises are associated with specific acoustic-prosodic profiles and strategies. We hypothesize that analyzing and assessing these profiles and strategies allows us to predict communicative skills. To that end, we used two analysis methods, one for charismatic and persuasive public speaking (PASCAL), and one for cooperative communication (DPA). PASCAL and DPA competency scores are determined on an acoustic basis for speech recordings of 21 students whose task was to co-create, in 7 teams of 3 students, a fully functioning weather station over 14 weeks in an Electrical Engineering project course - and to jointly write a development report about it afterwards. Results show that the students' PASCAL scores are significantly correlated with both the grade in their final oral project presentation and the grade of their written report as assessed by an independent lecturer group. The DPA scores correlate with better time-management and team working as well as with the quality and functionality of the designed product. Explanations for the links between student performance and acoustic competence scores are discussed.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Computational paralinguistics; Human-computer interaction; Speech recognition; Voice profiling

Towards the prosody of persuasion in competitive negotiation. The relationship between f0 and negotiation success in same sex sales tasks - Michalsky, Jan; Schoormann, Heike; Schultze, Thomas (Proceedings of the Annual Conference of the International Speech Communication Association, INTERSPEECH, 2019)
Prosodic features play a key role in a speaker's persuasive power. However, previous studies on persuasion have been focused on public speaking and the signaling of leadership, while acoustic studies on negotiation have been primarily concerned with cooperative interactions. In this study we are taking a first step into investigating the role of acoustic-prosodic cues in competitive negotiation, focusing on f0 in same-sex negotiations. Specifically, we ask whether the prosodic correlates of persuasive speech are comparable for public speaking and negotiation. Sixty-two speakers (44f/18m) in 31 same-sex pairs participated in a competitive task to bargain over the selling price of a fictional company. We find a significant correlation between a speaker's f0 features and his/her interlocutor's concession range. In line with findings from public speaking, greater f0 excursions and higher f0 minima correlate with negotiation success. However, while the female speakers also show an expected elevated f0 mean, the opposite is the case for male speakers. We propose that in competitive negotiation, displaying dominance may overrule showing passion in contrast to public speaking, but only for male speakers.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Charisma; Competitive negotiation; F0; Persuasion; Prosody; Sociophonetics; Voice profiling